Social Support for Success of Medication in Patients with TB MDR in Rumah Sakit Paru Dr. Ario Wirawan Salatiga, Central Java - Harni Seyla Anugerahni (Journal of Educational, Health and Community Psychology, 2020)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. In 2015, incidence of pulmonary tuberculosis in Salatiga ranks at 4th. The treatment occurs for about 6 – 8 months makes patient sometimes do not take the medicine regularly, which raised new problem that resistance to anti-tuberculosis drugs. The purpose of this study was to determine how the role of people those closest to the patient in order to support the treatment undergone by the patient, especially in the supervision of drug consumption and how the forms of the support given to patients that affect the treatment. This study uses qualitative method with case study approach. Participants were 8 people divided into 3 groups. Data obtained through depth interviews with family or the closest people who directly involved the patient during treatment period. The data were analyzed by content analysis.The results showed that social support less influence the success of treatment in patients with MDR TB